Knowledge of sunlight exposure toward obesity in geriatric - Amelia Lorensia; Rivan Virlando Suryadinata; Nurul Fitrianingsih (Universitas Muhammadiyah Malang, 2020)
Indonesia gets good sun exposure every year. Sunlight is a major source of vitamin D., but studies show that tropical countries still have a high prevalence of vitamin D deficiency. Geriatrics and obesity are some of the factors that can lead to vitamin D deficiency. Lack of information and knowledge about the effects of vitamin D deficiency, concerns about skin cancer from sunburn, and some current trends that want white skin cause them to limit sun exposure. Based on the high prevalence of geriatric and obesity data in Indonesia and the decline of functional status in geriatrics, which is a person's ability to perform daily physical activity, thus limiting himself to outdoor physical activities to expose the sun. Researchers conducted research to see the knowledge of sun exposure. This study was conducted to analyze vitamin D deficiency risk factors by the cross-sectional method to 88 obesity geriatrics and 88 non-obesity geriatrics based on knowledge of sun exposure. Test the risk factor aspects of knowledge using the odds ratio. The result of the odds ratio test of the knowledge aspect is 0.725, so it can be concluded that good knowledge of sun exposure has the same risk in both groups of respondents (obesity and non-obesity).